PERSEPSI PENONTON CHANNEL YOUTUBE NAJWA SHIHAB PADA KONTEN “30 TAHUN DEWA 19: MENDEKATI KEABADIAN” - Wicaksono, Tri Suci Putra; Sarjono, Herning Suryo; Kusumo Aji, Haryo (Solidaritas, 2024)
"30 Years of God 19: Approaching Eternity" is one of Najwa Shihab's YouTube video content which has been watched more than 1.9 million times and received 6,538 comments. From all the times I have watched the video, each viewer has a different perception. The aim of this research is to find out and describe the perceptions of Najwa Shihab's YouTube channel viewers on the YouTube content "30 Years of Dewa 19: Approaching Eternity". This research is a type of qualitative research with a descriptive approach. The object of this research is the audience's perception of Najwa Shihab's YouTube content entitled "30 Years of Dewa 19: Approaching Eternity" which was uploaded on 12 February 2023. The data in this research is the audience's perception of Najwa Shihab's YouTube content entitled "30 Years of Dewa 19: Approaching Immortality" obtained through interviews with informants selected using purposive sampling techniques. Data collection techniques in this research include in-depth interview techniques, observation and documentation. The data validity technique in this research uses triangulation techniques. Meanwhile, the data analysis technique in this research uses qualitative analysis. The results of this research found that informants perceive Dewa 19 as a legendary band that has been able to maintain its existence to this day. This is proven through Najwa Shihab's documentary video entitled "30 Years of Dewa 19: Approaching Eternity" which is proof of the existence of Dewa 19 which was able to survive up to 30 years, even though in its journey Dewa 19 has changed personnel several times. There are several factors that influence the perceptions of the informants, namely the objects perceived and the experiences of the informants.